GAMBARAN DARAH MERAH IKAN PATIN SIAM (Pangasius hypopthalmus) YANG DIBERI PAKAN MENGANDUNG PROPOLIS - Purwanto, Purwanto; Lukistyowati, Iesje; Riauwaty, Morina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis reseach was conducted in March-June 2018 in Fish Diasease and Parasite Laboratories and Experiment of the faculty of Fisheries and Marine Science University of Riau. The purpose of this study was to determine the effect of the description of red blood (total erythrocytes, hemoglobin, and hematocrit) and the growth of catfish (Pangasius hypopthalmus). The method used was experiment with Completely Randomized Design (RAL) with one factor, the level 5 treatments and 3 replications. The treatment in this study is, P0: control without given, P1 (addition of propolis in feed at a dose of 600 ppm/kg), P2 (700 ppm/kg), P3 (800 ppm/kg), P4 (900 ppm/kg). The parameters measured were total erythrocytes, hemoglobin levels, hematocrit values, absolute weight growth, fish survival, and water quality. The results showed that feeding containing propolis given for 60 days in catfish (Pangasius hypophthalmus) gave a significant effect on the number of erythrocytes, hemoglobin levels, hematocrit values, absolute weight growth with P <0.05 and not significantly different from fish survival P> 0.05. The best treatment at the dose of P3 (800 ppm) with total erythrocytes 276 x 104cells / mm3, hemoglobin levels of 10.6 g / dL, and hematocrit levels 33.3%, and absolute weight growth of 39.18 gr, and survival of 98 %. The results of measurements of water quality during the study were temperatures ranging from 27-310C, DO ranged from 3.4 to 3.9 ppm, pH ranged from 5.2 to 7, and NH3ranged from 0.017 to 0.024 ppm.Keywords: Propolis, Haematology, Pangasius hypopthalmus